Clinical Experiences of Amplitude-integrated Electroencephalographic Monitoring in Neonatal Intensive Care Unit - Lee, Sangeun; Choi, SuJin; Lee, Yun Jeong; Kim, Jisook; Park, Sook-Hyun; Lee, Eun Joo (Perinatology (Online), 2020)
Objective: The aim of this study was to analyze the relationship between maternal origin and risks of term low birth weight (TLBW) or macrosomia in Korea. Methods: Using Korean birth statistics from 2009 to 2015, we examined the association between maternal nationality and risks of TLBW (less than 2.5 kg) or term macrosomia (over 4.0 kg). Birth statistics included singleton live births in women, from 37 to 41 weeks’ gestation, during the period 2009-2015. Immigrant mothers were defined as women born in any country other than Korea, and were grouped by economic level of maternal country of origin. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated with multivariate logistic regression analysis. Results: There were significant differences in neonatal birth weights between Korean mothers and immigrant mothers (3.28±0.38 kg vs. 3.24±0.39 kg, P<0.001). In multivariate logistic regression analysis, the risk of TLBW was significantly higher (OR: 1.268, 95% CI: 1.181-1.361, P<0.001) and the risk of macrosomia was significantly lower (OR: 0.607, 95% CI: 0.518-0.71, P<0.001), in mothers from low and lower middle income countries, compared to Korean mothers. The risk of macrosomia was significantly higher (OR: 1.387, 95% CI: 1.228-1.566, P<0.001) and the risk of TLBW was significantly lower (OR: 0.879, 95% CI: 0.81-0.954), in mothers from high and upper middle income countries, compared to Korean mothers. Conclusion: After adjustment for relevant characteristics, the risk of TLBW was higher in immigrant mothers from low and lower middle income countries, but the risk of macrosomia was higher in immigrant mothers from high and upper middle income country. Prenatal care and education needs to consider the origin of immigrant mothers. KCI Citation Count: 0